Hyaluronan suppresses lidocaine-induced apoptosis of human chondrocytes in vitro by inhibiting the p53-dependent mitochondrial apoptotic pathway - Lee Yoon-Jin; Kim Soo A; Lee Sang-Han (Acta Pharmacologica Sinica, 2017)
Aim: Intra-articular injection of local anesthetics (LAs) is a common procedure for therapeutic purposes. However, LAs have been found toxic to articular cartilage, and hyaluronan may attenuate this toxicity. In this study we investigated whether hyaluronan attenuated lidocaine-induced chondrotoxicity, and if so, to elucidate the underlying mechanisms. Methods: Human chondrocyte cell line SW1353 and newly isolated murine chondrocytes were incubated in culture medium containing hyaluronan and/or lidocaine for 72 h. Cell viability was evaluated using MTT assay. Cell apoptosis was detected with DAPI staining, caspase 3/7 activity assay and flow cytometry. Cell cycle distributions, ROS levels and mitochondrial membrane potential (ΔΨm) were determined using flow cytometry. The expression of p53 and p53-regulated gene products was measured with Western blotting. Results: Lidocaine (0.005%−0.03%) dose-dependently decreased the viability of SW1353 cells. This local anesthetic (0.015%, 0.025%) induced apoptosis, G2/M phase arrest and loss of ΔΨm, and markedly increased ROS production in SW1353 cells. Hyaluronan (50−800 μg/mL) alone did not affect the cell viability, but co-treatment with hyaluronan (200 μg/mL) significantly attenuated lidocaine-induced apoptosis and other abnormalities in SW1353 cells. Furthermore, co-treatment with lidocaine and hyaluronan significantly decreased the levels of p53 and its transcription targets Bax and p21 in SW1353 cells, although treatment with lidocaine alone did not significantly change these proteins. Similar results were obtained in ex vivo cultured murine chondrocytes. Conclusion: Hyaluronan suppresses lidocaine-induced apoptosis of human chondrocytes in vitro through inhibiting the p53-dependent mitochondrial apoptotic pathway.